Losses related to infectious diseases in the Turkish army during World War I - Karakus, Sadik Emre; Basustaoglu, Ahmet C. (Csiro Publishing, 2014)
The lengthy period that encompasses the Balkan War (8 October 1912 to 29 September 1913), followed by WWI (28 July 1914 to 30 October 1918) fought by the Ottoman Empire and the subsequent Turkish War of Independence initiated by the secret arrival of the great leader Mustafa Kemal (in the Republican era Ataturk) at the Black Sea town of Samsun on 19May 1919 came to an end with the signing of the Mudanya Agreement on 11 October 1922 and formally terminated with the Lausanne Agreement on 24 July 1923. Turks bravely fought at different fronts over three different continents and by the end of a decade of war the losses amounted to 1,000,000 lives as well as 4,000,000 square meters of the Ottoman Land1.